Pengaruh Sistem Pengendalian Internal Pemerintah dan Whistleblowing System Terhadap Pencegahan Fraud Dalam Pengelolaan Dana Bantuan Operasional Sekolah - Siti Solihatunnisa; Hastusi Hastuti (Indonesian Accounting Research Journal, 2023)
The purpose of this study was to determine the effect of the Government lnternal Control System (SPIP) and Whisleblowing System on fraud prevention in managing BOS funds. This is because there are stil problems in managing BOS funds in the Ministry of Religion, especially the MTS in Bandung Kulon District. The research method used is descriptive quantitative. The population, is MTS in Bandung Kulon District with a sample of 7 Madrasahs with 34 respondents. The data source used is primary data in the form of distributing questionnaires. The analytical method used is the path analysis method and its processing uses SPSS 25. The results show that SPIP has a positive and significant efect on whistleblowing system, whistle blowing system has a positive and significant effect on SPIP, SPIP has a positive and significant effect on fraud prevention in the management of BOS funds, whistleblowing system has a positive and significant effect on fraud prevention. in the management of BOS funds, SPIP and whistleblowing system simultaneously lnfluence on fraud prevention in management of BOS funds in MTS Bandung Kulon District.